Prevalence and predictors of medication non-adherence in some common non-communicable chronic diseases and cancers: a comparative study - Mir, Shakeel A.; Shakeel, Danish (International Journal of Basic & Clinical Pharmacology, 2020)
Background: Adherence is a key factor in the success of all pharmacological therapies. Medication non-adherence is an extremely common barrier to achieve positive health outcomes. The present study aims to compare medication non-adherence in some common chronic diseases and cancers and also to assess various factors influencing it. Methods: Pre-validated questionnaires based on general medication adherence scale (GMAS) were equally distributed among 300 patients suffering from chronic illnesses and cancers. 270 patients returned completely filled questionnaires. Results: The study population consists of 53.33% men and 46.66% women.55.55% patients were literate. 70.37% of patients were from rural areas. 61.48% were taking 2-4 drugs. As compared to 14.81% males 18.51% of females had poor or low adherence. Only 0.74% of young patients (<30 years) had poor/low adherence as compared to 16.29% each in other age groups. Rural patients had poor adherence as compared to patients from urban areas. As compared to 31.85% illiterate patients, only 16.29% of literate patients had poor or low adherence. Adherence was better in patients taking more than one drug. Statistically, a significant correlation was found between gender, age, level of education, and area of residence. Duration of treatment, the number of drugs, and the frequency of dosage were not found significantly correlated with adherence. Patients suffering from malignancies had higher medication adherence as compared to chronic illnesses. Conclusions: Medication non-adherence is common in patients with chronic diseases and cancers that are treated with unsupervised oral antineoplastic drugs. The complex problem of non-adherence calls for interventions at various levels.